Analisis Pengaruh Pariwisata Budaya Terhadap Pelestarian Suku Osing di Desa Wisata Kemiren - Fatihika Endriana; Shanaz Citra Alnauri; Debby Angely Agustin (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
Cultural diversity in East Java is a leading potential in tourism activities, this is because the culture is unique and has its own characteristics in each region. One of them is Banyuwangi which is located in the eastern part of Java Island and is nicknamed The Sunrise of Java, making Banyuwangi transformed into a tourist area that develops through the artistic potential and local wisdom of the Osing Tribe. The Osing tribe is a native of Banyuwangi and is considered the original Osing tribe, a sub-ethnic of the Javanese tribe. One of the villages in Glagah District has residents who still preserve the traditional values ​​and customs of Osing, namely Kemiren Village. With that, Kemiren Village has the potential to become a cultural tourism object with the Osing Tribe's cultural attractions. However, this study will use a qualitative descriptive method to analyze the actual situation or facts. Primary data and secondary data are used to support this research. This study found that the influence of tourism on the preservation of the Osing Tribe culture in Kemiren Village received a positive response from informants who were taken directly through interviews with one of the Osing indigenous people in Kemiren Village. The local community said that the existence of a tourist village for them did not interfere with their activities. According to them, the presence of a village tourism village is able to develop community innovation, namely the emergence of employment opportunities and a significant economic improvement for the people of Kemiren Village. In addition, from a socio-cultural perspective, the people of Kemiren Village maintain their daily lifestyle and preserve the traditions or customs that apply in the village.